Tectonic Significance of Mylonites from Mingora, Swat - Humayun, Munir (Journal of Himalayan Earth Sciences, 1985)
Rocks below the Swat gneisses, formarely thought to be a single unit, are a varied assortment of thrust slices consisting of rapakivi granites, sillimanite gneisses, marbles, and schists, in a mylonite zone. This zone is interpreted as the bare of a large thrust. Thus, the overlying Swat gneisses and associated schists constitute a crystalline thrust sheet or nappe (?), that probably formed in response to the obduction of the Kohistan island arc.